Notes on health as balance, harmony and equilibrium - Lee, Zosimo E. (1997)
This paper looks at the concept of health as the interaction between the body and the mind from the perspective of the concepts of balance, harmony and equilibrium. The notion of disease is a key to understanding ill-health.
Includes bibliographical references.
Keywords: Health; Mind body relations